2014
DOI: 10.1097/mca.0000000000000105
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural red blood cell distribution width predicts bare metal stent restenosis

Abstract: Increased preinterventional RDW significantly predicts bare metal stent restenosis and might represent a useful screening tool to stratify patients according to a higher or a lower risk of ISR after stent implantation in patients with stable and unstable angina pectoris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
(38 reference statements)
0
9
0
1
Order By: Relevance
“…37 In a recent study, an increased RDW predicted BMS restenosis suggesting potential as a useful screening tool to stratify patients by higher or lower risk of ISR. 38 The underlying mechanism of the relationship between RDW and DES restenosis remains undefined. In the present study, although RDW was higher in the ISR group, no significance was apparent in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…37 In a recent study, an increased RDW predicted BMS restenosis suggesting potential as a useful screening tool to stratify patients by higher or lower risk of ISR. 38 The underlying mechanism of the relationship between RDW and DES restenosis remains undefined. In the present study, although RDW was higher in the ISR group, no significance was apparent in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important limitations affecting the long-term outcomes of CAD invasive treatment is restenosis [ 70 ] which occurs more frequently in patients with elevated RDW values, which is the case following both bare-metal [ 61 ] and antimitotic drug-eluting stent implantation [ 64 ]. RDW is also valuable in assessing the risk of major bleeding complications in patients undergoing PCI [ 60 ], as well as the risk of contrast-induced nephropathy [ 65 ].…”
Section: The Prognostic and Diagnostic Value Of Rdw In Cadmentioning
confidence: 99%
“…The underlying mechanism of the relationship between RDW and DES restenosis is still not clearly elucidated. A recent study showed that an increased RDW significantly predicts bare metal stent restenosis and might represent a useful screening tool to stratify patients according to a higher or a lower risk of ISR after stent implantation in patients with stable and unstable angina pectoris [16]. In the present study, we have determined that RDW and CRP levels were higher in the ISR group and both of these biomarkers were independently associated with the presence of DES restenosis.…”
mentioning
confidence: 60%